Performance of zero water discharge (ZWD) system with nitrifying bacteria Bacillus megaterium and microalgae Chaetoceros calcitrans components in super intensive pacific white shrimp Litopenaeus vannamei culture at low salinity - Rahim, Rahim; Suantika, Gede; Muhammad, Harish (Indonesian Society of Scientific Aquaculture (ISSA), 2018)
ABSTRACTThis research aimed to obtain the performance of super intensive white shrimp rearing using zero water discharge (ZWD) system. This study consisted of four steps, (1) activation and cultivation of nitrifying bacteria, microalgae C. calcitrans and B. megaterium; (2) acclimatization of Pacific white shrimp PL10 with 30 g/L of salinity and decreasing salinity at 2–3 g/L/day; (3) conditioning of ZWD system; (4) white shrimp rearing in 400 L of tank for ten weeks. The experiment used three treatments, (a) shrimp reared without any addition of microbial agent with water exchange conducted every week as much as10–20% of total rearing volume as control (K); (b) ZWD systems with the applications of nitrifying bacteria, (C. calcitrans and B. megaterium) without water discharge (P1); and (c) ZWD system with the application of microalgae C. calcitrans and B. megaterum without water discharge (P2). According to the results, application of nitrifying bacteria, microalgae C. calcitrans and B. megaterium were able to improve the performance of ZWD system performance of white shrimp rearing at low salinity. In addition, the ZWD system was also able to increase the growth rate and survival rate of shrimp when it compared to control. The best rearing performance was found in ZWD system with application of microalgae C. calcitrans and B. megaterium. Keywords: Litopenaeus vannamei, ZWD, low salinity, microalgae, nitrification bacteria. ABSTRAKPenelitian ini bertujuan untuk mengetahui kinerja budidaya udang putih super intensif bersalinitas rendah menggunakan sistem zero water discharge (ZWD). Penelitian ini terbagi dalam tiga, yaitu (1) aktivasi dan kultur bakteri nitrifikasi, mikroalga C. calcitrans dan B. megaterium; (2) aklimatisasi udang putih PL10 salinitas 30 g/L dan penurunan salinitas 2–3 g/L/hari; (3) pengondisian dari sistem ZWD; (4) pemeliharaan udang putih selama 10 minggu di bak bervolume 400 L. Penelitian ini menggunakan tiga perlakuan ; (a) perlakuan kontrol tanpa penambahan mikroba dan pergantian air setiap minggu sebanyak 10–20% (K) ; (b) sistem ZWD dengan bakteri nitrifikasi, mikroalga C. calcitrans dan B. megaterium tanpa pergantian air (P1); (c) sistem ZWD dengan mikroalga C. calcitrans dan B. megaterum tanpa pergantian air (P2). Berdasarkan hasil yang didapat, aplikasi bakteri nitrifikasi, mikroalga C. calcitrans dan B. megaterum mampu meningkatkan kineja sistem ZWD pada budidaya udang putih L. vannamei bersalinitas rendah. Selain itu, aplikasi bakteri nitrifikasi, mikroalga C. calcitrans dan B. megaterum pada sistem ZWD juga mampu meningkatkan laju pertumbuhan dan sintasan udang putih dibanding dengan kontrol. Kinerja pemeliharaan terbaik dijumpai pada sistem ZWD dengan aplikasi mikroalga C. calcitrans dan B. megaterum. Kata kunci: bakteri nitrifikasi, Litopenaeus vannamei, mikroalga, salinitas rendah, ZWD